Система управления электроприводом питателя шаровой барабанной мельницы - Садовой, Александр Валентинович; Тищенко, Николай Тарасович; Тищенко, Евгений Викторович (НТУ "ХПИ", 2010)
On the basis of a mathematical model of ball mill drum designed control algorithm provides stability control system load capacity of the mill drum as in the ascending and the descending branch of the mill. A block diagram of control system of ball mill drum with PID controller level designed in this paper.
The control system electric drive feeder ball mill drum
Keywords: уголь сырой; пыль угольная; баланс; коррекция